Presentation is loading. Please wait.

Presentation is loading. Please wait.

Solve an equation 7y – 6y + 12 = 4y. Simplify 7y – 6y + 12 = 4y 7y – 6y + 12 = 4y becomes y + 12 = 4y when we combine like terms.

Similar presentations


Presentation on theme: "Solve an equation 7y – 6y + 12 = 4y. Simplify 7y – 6y + 12 = 4y 7y – 6y + 12 = 4y becomes y + 12 = 4y when we combine like terms."— Presentation transcript:

1 Solve an equation 7y – 6y + 12 = 4y

2 Simplify 7y – 6y + 12 = 4y 7y – 6y + 12 = 4y becomes y + 12 = 4y when we combine like terms

3 Collect Get variables together y + 12 = 4y since there are fewer y’s on the left I move the single y on the left by subtracting y y – y + 12 = 4y – y which becomes 12 = 3y

4 Isolate and Solve 12 = 3y the variable is already isolated so all we have left to do is solve – divide by whatever is with the y 12 = 3y 3 This becomes 4 = y

5 Check Guarantee yourself that you are correct by checking your solution in the original equation. 7y – 6y + 12 = 4y Everywhere you have a y put what you found y to equal and simplify 7(4) – 6(4) + 12 = 4(4) Simplify 28 – 24 + 12 = 16 4 + 12 = 16 16 = 16


Download ppt "Solve an equation 7y – 6y + 12 = 4y. Simplify 7y – 6y + 12 = 4y 7y – 6y + 12 = 4y becomes y + 12 = 4y when we combine like terms."

Similar presentations


Ads by Google